Is non-mentored initiation of laparoscopic colorectal surgery safe? Single surgeon initial experience with the first 40 cases - Bakula, Branko (Frontiers in Surgery, 2023)
Although laparoscopic colorectal surgery is now accepted as a standard procedure in the treatment of colorectal cancer, the proportion of laparoscopically operated patients with colorectal cancer is still generally quite low. The aim of this study was to asses feasibility, safety and outcomes of non-mentored initiation of laparoscopic colorectal resections by young surgeon with no previous experience in laparoscopic colorectal surgery.We analyzed the characteristics of the first 40 elective laparoscopic colorectal resections performed by a single surgeon during the period between June 2019 and March 2022. All of the operations were performed without the attendance or supervision of a surgeon with experience in laparoscopic colorectal surgery. The patients were divided into three groups (early, intermediate and late group).The conversion rate, complications rate and postoperative recovery were similar between groups. The mean overall operative time was 219.5 min (range 130-420 min) and was reduced significantly during the learning curve (p = 0.047). Overall conversion rate was 12.5%. In two cases (5%) oncological principals were violated (incomplete TME). In three patients (7.5%) intraoperative complications occurred (small bowel injury, splenic injury and significant bleeding from minor peripancreatic artery). Three cases of major postoperative complications (Clavien-Dindo III grade) were recorded, two of which required reoperation (anastomotic bleeding and fascial dehiscence). There was no 90-days mortality. The overall mean number of lymph nodes retrieved was 12.45 and did not differ significantly between groups (p = 0.678). The average follow-up was 13.75 months (range 1-31 months). Cancer recurrence was recorded in four patients (10%). Port site metastasis was not detected in any case.Safe non-mentored initiation of laparoscopic colorectal surgery with an acceptable rate of complications and acceptable oncological results can be achieved. Still, when compared with structured initiation in controlled environment with the supervision of an experienced laparoscopic colorectal surgeon results are worse in most of the fields including operative time, conversion rate, complications rate and duration of hospital stay.Therefore, I strongly recommend engaging young surgeons in structured laparoscopic colorectal surgery fellowship programs whenever possible before starting performing these procedures on their own.